Atendimento a normas de segurança e ergonomia nos postos de operação de tratores agrícolas - Barbieri, Juan Paulo (2017)
In modern agriculture, the agricultural tractor is an essential equipment for the accomplishment of the numerous agricultural operations of a property. Since the first tractors with internal combustion engine, big transformations have occurred in their projects, and the operating station where the most notable changes, as systems are constantly undergoing updates, and the manufacturers thinking about the comfort of the operator and the compliance with national and international regulations. The objective of this work was to evaluate and compare the conformity of the new agricultural tractors commercialized in the Brazilian market, with the specifications standardized by national and international standards of safety and ergonomics, qualifying the operating stations with the created of an ergonomic index. The agricultural tractors were divided into classes according to the gross power in the engine. In the agricultural tractors, the operating controls were measured in relation to the Seat Index Point, the measures of access and exits of the operation station, besides observing the presence of obligatory items in agricultural tractors. The main results show that Class VI agricultural tractors (above 200 CV) showed the highest compliance with ISO 15077, with regard to the internal position of the controls in the operating station. Between the controls, the gear lever was the one that best complied with the ISO 15077. As for the compliance with the ABNT NBR ISO 4254-1, the tractors without cabin had less conformity than the cabin. All the operating stations had at least two emergency exits, as required by ABNT NBR 4252. Most of the mandatory items provided for in NR 12 are present or agreed at the farm tractor stations evaluated. The 4CC operating station presented the best Ergonomic Index among the sampled operating stations and the 2NA Operational Station presented the lowest Ergonomic Index and it was efficient in terms of feasibility and can be applied to other models of agricultural tractors and machines.